PENGARUH PENGGUNAAN APLIKASI WHATSAPP DAN GOOGLE CLASSROOM TERHADAP HASIL BELAJAR SISWA SMP SWASTA KARTIKA 1-4 PEMATANGSIANTAR TAHUN AJARAN 2021/2022 - Jayanti, Fitri Dwi; Piliang, Fenny Mustika; Damanik, Risjunardi (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2024)
This study aims to examine the Effect of Using WhatsApp and Google Classroom Applications on Student Learning Outcomes. This study is a quantitative study. The study population was 105 students consisting of 3 classes. Sampling was carried out by Cluster Random Sampling, namely class VIII-A using the WhatsApp application and VIII-B using the Google Classroom application, the number of each class was 35 students. The research instrument used a test. Based on the results of hypothesis testing using the t test, as obtained tcount 5.511> ttable (1.994) at a significance level of 0.000 <0.05. Based on this, it can be concluded that the Sig. value <0.05 and the tcount value> ttable, which means that H_0 is rejected and 〖 H〗_a is accepted, thus there is a significant influence between the values in the experimental class and the values in the control class. Based on the results of hypothesis testing using the F test, as obtained the Fcount value is greater than Ftable (15.201> 3.128) and the sig. value. smaller than 0.05 (0.003 <0.05). Thus, Ha is accepted and H0 is rejected, meaning that there is a significant influence if learning is carried out using the WhatsApp and Google Classroom applications on the learning outcomes of class VIII students of SMP Swasta Kartika 1-4 Pematang Siantar in the 2021/2022 academic year.